Analisis Kesenjangan Kompetensi SDM dalam Industri Ekonomi Kreatif di Era Digital: Strategi dan Implikasi Pengembangan - Dykha Arda Wiranata; Mohammad Robbi Zidni Firmansyah; Angga Jibrilda Syahrial (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The creative economy industry serves as a strategic pillar of the national economy, experiencing significant transformation in the digital era. This study aims to comprehensively analyze the pattern of human resource (HR) competency gaps within priority subsectors of Indonesia's creative economy and formulate effective, multi-stakeholder development strategies. Employing a Systematic Literature Review (SLR) methodology, this research rigorously analyzes 30 scientific journal articles, government reports, and publications from global institutions published between 2014 and 2024. The findings delineate three primary clusters of competency gaps: (1) The Digital-Technical Competency Gap, encompassing deficiencies in data analytics, specialized software mastery, and digital content creation tools; (2) The Digital-Business Competency Gap, which includes shortcomings in digital financial literacy, online business model development, and management of digital intellectual property rights; and (3) The Social-Cognitive Competency Gap, highlighting needs in adaptability, complex problem-solving, and effective virtual collaboration. In response, this paper proposes an integrative strategic framework grounded in a collaborative multi-stakeholder approach. Key recommendations include revitalizing educational curricula through industry-embedded learning and micro-credential integration, developing agile and accessible training ecosystems featuring bootcamps and digital platforms, and fostering supportive policies through fiscal incentives and the alignment of national qualification frameworks with digital skill standards. The successful implementation of this synergistic strategy is expected to significantly enhance the adaptability, innovation capacity, and global competitiveness of Indonesia's creative workforce, thereby ensuring the sustainable growth of the creative economy sector in the face of rapid digital disruption.